Growth and accumulation of nutrients in organic jambu - Grangeiro, Leilson Costa; Souto, Gilberta Carneiro; Sousa, Valdivia Fátima Lima; Carneiro, Jader Vieira; Silva, Jorge Luiz Alaves; Santos, Jandeilson Pereira (Comunicata Scientiae, 2018)
The objective of this study was to evaluate the growth and accumulation of nutrients in accessions of organic jambu. The experiment was conducted in the didactic garden of the Federal Institute of Pará, Campus Castanhal, in the period May and June 2015. The experimental design was a randomized complete block design with a 2 x 5 factorial arrangement with four replicates. The treatments were a combination of two jambu accessions (Purple Flower and Yellow Flower) and five sampling times (10, 18, 26, 34 and 42 days after transplanting - DAT). The period of greatest growth and nutrient demand was for access to Purple Flower from 18 to 34 DAT and for the Yellow Flower from 26 to 42 DAT. Nutrient accumulation by the two accesses of jambu, in decreasing order, was: potassium, nitrogen, calcium, magnesium and phosphorus.